2019
DOI: 10.1002/asi.24242
|View full text |Cite
|
Sign up to set email alerts
|

Neuropsychological model of the realization of information need

Abstract: The main goal of Information Retrieval (IR) is to satisfy information need (IN). IN refers to a complex concept: at the very initial state of the phenomenon (i.e. at a visceral level), even the searcher may not be aware of its existence. Thus despite advances in the past few decades in both the IR and relevant scientific communities, we do not fully understand how an IN emerges and how it is physically manifested. In this paper, we aim to inform a holistic view of the realisation of IN using functional Magneti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 65 publications
0
13
0
Order By: Relevance
“… Day (2010) explored the effectiveness of applying the Needleman–Wunsch algorithm in identifying decision-making strategies using eye movement data. Moshfeghi and Pollick (2019) analyzed consumer demand for information retrieval and discovered brain regions related to inform decision-making through brain activity-related data. This study aims to understand consumers’ demand for information.…”
Section: Resultsmentioning
confidence: 99%
“… Day (2010) explored the effectiveness of applying the Needleman–Wunsch algorithm in identifying decision-making strategies using eye movement data. Moshfeghi and Pollick (2019) analyzed consumer demand for information retrieval and discovered brain regions related to inform decision-making through brain activity-related data. This study aims to understand consumers’ demand for information.…”
Section: Resultsmentioning
confidence: 99%
“…A rise in adoption of neuroimaging techniques across the key areas of IS&R resulted in numerous NeuraSearch applications with the most notable being relevance judgment [46,47], IN realisation [20], search transitions [23] or query construction [48]. Commonly used neuroimaging techniques include electroencephalography (EEG) [46,[48][49][50][51][52], functional magnetic resonance imaging (fMRI) [20,22,49], magnetoencephalography (MEG) [53], functional Near Infrared Spectroscopy (fNIRS) [54,55]. The EEG studies manifested the effectivity of EEG to capture the brain activities of complex cognitive processes utilising its fine-grained temporal resolution.…”
Section: Relevant Workmentioning
confidence: 99%
“…To tackle this problem, new research has emerged employing neuroimaging techniques to directly monitor brain activity of subjects experiencing a realisation of IN [20][21][22]. This research has led to a discovery of cognitive processes and brain regions associated with the realisation of IN [22,23]. However, these studies have used fMRI technique which has a high spatial, but low temporal resolution.…”
Section: Introductionmentioning
confidence: 99%
“…A collection of fMRI studies by Moshfeghi and colleagues (Moshfeghi et al, 2013, 2016; Moshfeghi & Pollick, 2019, 2018; Moshfeghi, Triantafillou, & Pollick, 2019) has focused on using fMRI to understand the brain regions activated during relevance judgment and IN. Results from one study (Moshfeghi et al, 2013) revealed the brain regions that are activated during the relevance judgment process.…”
Section: Related Workmentioning
confidence: 99%